Observation of single photon interference and Hong-Ou-Mandel dip - P, Munkhbaatar; Ts, Baatarchuluun; D, Ulam-Orgikh; J, Davaasambuu; K, Myung-Whun (Scientific transaction of the National University of Mongolia. Physics, 2022)
We have built a cost effective Hong-Ou-Mandel (HOM) interferometer by using a conventional cheap multimode laser and a home-made coincidence counting circuit and we have observed the single photon interference and HOM dip making us to measure the bandpass filter. We expect it could be a good model to the graduates trying a variety of quantum optics experiments.